Vascular injuries during gynecological laparoscopy: the vascular surgeon’s advice - Barros, Marcello Barbosa (2005)
CONTEXT: Iatrogenic vascular problems due to laparoscopy are a well recognized problem and lead to signiﬁcant repercussions. In this context, a ten-year review of cases topic is presented, based on experience gained while heading two important vascular surgery services. CASES: Five patients with vascular injuries during elective laparoscopy are described. These patients presented with seven lesions of iliac vessels. All cases were evaluated immediately and required laparotomy, provisional hemostasis and urgent attendance by a vascular surgeon. Direct suturing was performed in three cases. One aortoiliac bypass and one ilioiliac reversed venous graft were made. Venous lesions were sutured. One case of a point-like perforation of the small bowel was found. There were no deaths and no complications during the postop- erative period. DISCUSSION: Important points on this subject are made, and advice is given. There needs to be immediate recognition of the vascular injury, and expert repair by a vascular surgeon is rec- ommended, in order to signiﬁcantly reduce the degree of complications.